Social license to operate: An integrative framework - Baba, Sofiane; Dahan, Jacqueline (Management international / International Management / Gestiòn Internacional, 2023)
The literature generically addresses controversies related to the lack of social acceptance of projects, usually overlooking their specificities. We argue instead that each trajectory of social acceptance (or lack thereof) is unique. This article demonstrates this through a qualitative analysis of three controversial projects: Matoush uranium mining (2006-2020), Facebook’s cryptocurrency (2017-2021), and Covid-19 vaccination (2020-2021). We develop an analytical framework that conceptualizes social acceptance as a dynamic trajectory of legitimation and justification revolving around three pillars: eco-traditional, symbolic, and technical. This article enriches our understanding of social acceptance issues and offers new research perspectives at the interface of social acceptance, legitimation, and institutional logics.